Association between estimated glucose disposal rate and prediction of cardiovascular disease risk among individuals with cardiovascular-kidney-metabolic syndrome stage 0–3: a nationwide prospective cohort study - Jing Tian; Hu Chen; Yan Luo; Zhen Zhang; Shiqiang Xiong; Hanxiong Liu (Diabetology & Metabolic Syndrome)
Abstract Background Insulin resistance is a crucial factor in the development of cardiovascular diseases (CVD), yet the relationship between the estimated glucose disposal rate (eGDR), an index reflecting insulin resistance, and the risk of new-onset CVD among individuals with cardiovascular-kidney-metabolic (CKM) syndrome stage 0–3 remains underexplored, and large-scale prospective cohort studies are needed to clarify this relationship. Methods All data for this study were extracted from the China Health and Retirement Longitudinal Study (CHARLS). The primary outcome was the incidence of new-onset CVD (including heart diseases (HD) and stroke) during the follow-up period (from 2013 to 2020). Multivariable logistic regression models were applied to elucidate the relationship between the eGDR and the risk of developing CVD. The restricted cubic splines (RCS), mediation analysis, and stratified analyses were also employed. Results This study included 6752 participants, of whom 1495 (22%) developed CVD. Odds ratios and 95% confidence intervals from lowest eGDR level (<7.37 mg/kg/min) to highest eGDR level (≥ 11.16 mg/kg/min) were 1.00 (reference), 0.81 (0.68, 0.96), 0.72 (0.58, 0.88), and 0.74 (0.58, 0.94) respectively, for the occurrence of CVD; 1.00 (reference), 0.81 (0.67,0.97), 0.72 (0.57,0.90), and 0.75 (0.58,0.97) respectively, for the occurrence of HD; 1.00 (reference), 0.91 (0.74,1.12), 0.80 (0.62,1.04), and 0.71 (0.52,0.97) respectively, for the occurrence of stroke after adjusting for all potential covariates. The RCS analysis discovered an approximately inverse “L” correlation between eGDR and the occurrence of CVD and HD across all individuals with CKM syndrome stages 0–3 (All P for overall < 0.001, All P for nonlinear = 0.005), while there was a negative linear correlation between eGDR and the risk of new-onset stroke (P for overall = 0.026, P for nonlinear = 0.098). Furthermore, the proportions mediated through BMI were 41.98%, 43.05%, and 43.23% for CVD, HD and stroke, respectively. No significant interactions were found. Conclusions The eGDR was a novel indicator of new-onset CVD in individuals with CKM syndrome stages 0–3, with BMI serving as a partial mediator in the association between eGDR and CVD risk. Addressing insulin resistance may represent a viable strategy for reducing the risk of CVD in this population.